Nonmedical use of prescription drugs for cognitive enhancement as response to chronic stress especially when social support is lacking. (29th November 2018) - Sattler, Sebastian
Abstract: The nonmedical use of prescription drugs to improve cognitive performance has gained attention due to concerns over its social and political implications as well as side effects and long‐term health consequences. Some researchers expect a future trend of an instrumental use of drugs for cognitive enhancement (CE). Thus, getting insights about causes of CE‐drug consumption is warranted before the prevalence increases. Because perceived stress is ubiquitous in universities and may decrease cognitive performance, one reaction to cope with stress and its consequences might be the instrumental use of drugs for CE, especially if other resources, such as social support, are lacking. With a prospective design, randomly selected students from four German universities were invited to a web‐based survey and reinterviewed after 6 months ( N = 2, 203). Results show a 6‐month prevalence rate of self‐reported CE‐drug use of about 2%. Higher reported chronic stress is positively associated with CE‐drug use. Although social support has no main effect, stress‐buffering effects were found. In men with low stress, more support is associated with a higher chance of self‐reported CE‐drug use. These findings can inform intervention and prevention strategies such as changes in drug regulation or sensitizing (potential) users to unwanted health consequences.